2007
DOI: 10.1038/sj.bjc.6603728
|View full text |Cite
|
Sign up to set email alerts
|

Studies on p53, BAX and Bcl-2 protein expression and microsatellite instability in stage III (UICC) colon cancer treated by adjuvant chemotherapy: major prognostic impact of proapoptotic BAX

Abstract: We evaluated the expression patterns of proapoptotic BAX, antiapoptotic Bcl-2 and p53, the proposed upstream effector of these molecules, as potential prognostic markers in UICC stage III colon cancer by immunohistochemical staining. To identify highfrequency microsatellite instability (MSI þ ) individuals, we performed single-strand conformation polymorphism-based analysis for BAT26. A total of 188 patients who had received 5-fluorouracil (5-FU)-based adjuvant chemotherapy (5-FU/folinic acid or 5-FU/ levamiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 38 publications
3
43
1
1
Order By: Relevance
“…On the other hand, bcl-2 has been correlated with recurrence by some authors, although other studies have shown the same result as in the present study (19,20) . With regard to Ki-67, this study showed a statistically significant correlation between immunohistochemical expression of this protein and recurrence (P = 0.035).…”
Section: Discussioncontrasting
confidence: 36%
See 1 more Smart Citation
“…On the other hand, bcl-2 has been correlated with recurrence by some authors, although other studies have shown the same result as in the present study (19,20) . With regard to Ki-67, this study showed a statistically significant correlation between immunohistochemical expression of this protein and recurrence (P = 0.035).…”
Section: Discussioncontrasting
confidence: 36%
“…Among the present study sample, the immunohistochemical expression of bcl-2 was not significantly correlated with the degree of cell differentiation, and this has also been shown in some other studies (2) . On the other hand, a study by Nehls et al (20) showed a statistically significant correlation between bcl-2 and a high degree of cell differentiation. Despite this result, a clear difference was observed between the p53 and bcl-2 expressions, in comparison with tumor expression (85.4% and 31.7%) and degree of cell differentiation (84.6% and 32.1% when evaluating a low degree of differentiation).…”
Section: Discussionmentioning
confidence: 99%
“…Such segmental predilection is expected for markers involved in certain steps of the adenoma-carcinoma sequence (7,8,12), the dominant tumorigenic mechanism in CRC (2,22), followed by the large majority of distal tumors. By contrast, a significant part of proximal tumors, evolving through the genetically different microsatellite instability pathway and probably arising from different precursor lesions (serrated polyps) (3,28), usually lacked p53 and Bcl-2 expression (19,27,28). This assumption is also suggested by the reported site-specific prognostic significance of p53 and Bcl-2 (9,13).…”
Section: Discussionmentioning
confidence: 53%
“…There are data reporting that overexpression of Bcl-2 is related with down-regulation of Bax and the interruption in the progression of apoptosis is dependent to the imbalance of Bcl-2/Bax, which plays a role in cancer development [15,24,26] . It was reported that in some cancer types such as myeloid leukaemia [27] and cancers of prostate [28] , cervix [19] and colon [29] expression of Bcl-2 is increased. But in previous studies with human breast cancers, it was stated that Bcl-2 expression is generally observed in benign proliferative lesions and small, slowly progressing oestrogen-positive, p53-negative tumours and was found to be related with better prognosis [7,25,30] .…”
Section: Discussionmentioning
confidence: 99%